STRATEGI PENGEMBANGAN AGRIBISNIS JAGUNG MELALUI PENGUATAN KELOMPOK TANI DI KECAMATAN BUNGA MAYANG - Aisah, Zainul Adhar, Iman Sulaiman (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2026)
Bunga Mayang District is one of the maize production centers in East OKU Regency, yet farmers still face challenges such as low bargaining power and price fluctuations. This study aims to identify internal and external factors and formulate a maize agribusiness development strategy through strengthening farmer group institutions. The research was conducted in Bunga Mayang District in 2026. The research method used was descriptive qualitative with IFAS, EFAS, and SWOT matrix analysis. The results showed a total IFAS score of 2.60 and an EFAS score of 2.55. The strategic position for maize agribusiness development is in Quadrant I (Aggressive Strategy). The main strength is land suitability, while the greatest opportunity is the high demand from the feed industry. The resulting priority strategy is strengthening the role of farmer groups through strategic partnerships with the industry to shorten the supply chain and optimizing post-harvest technology assistance to increase product added value.